The Ability Lecturer of Historical Thinking in Historical Literature - Rimma Ramilievna Zamilova (Researchparks Publishing, 2021)
The research paper provides a methodology for teaching a lecturer where the process is the formation of historical thinking, the subject of research is the development of historical thinking in history lessons.